Determinan Keikutsertaan Perawat dalam Continuing Professional Development - Enny Sri Purwanti (Politeknik Karya Husada, 2024)
Continuing Professional Development (CPD) is needed by all nurses to support professional competence. This study aimed to identify the most dominant factors associated with nurses' participation in CPD. The research design used a cross-sectional approach involving 186 nurses at type B private hospitals in East Jakarta. Data collection used a modified instrument from the Modified Questionnaire-Professional Development of Nurses (Modified Q-PDN) to measure nurses' participation in CPD activities (Cronbach alpha= 0.926) and a determinant factor questionnaire developed by researchers referring to Imogene King's interaction systems theory (Cronbach alpha = 0.957). Bivariate analysis uses Spearman Rank and multivariate analysis uses multiple linear regression tests. Research found perception, self-image, family support, peer support, superior support, work environment, and organizational support were related to nurses' participation in CPD activities (p